PENYIDIKAN TERHADAP KASUS PENYALAHGUNAAN BAHAN BAKAR MINYAK MAUPUN LIQUEFIED PETROLEUM GAS DISUBSIDI PEMERINTAH - Pramana Putra, I Gede Indra (Kerta Dyatmika, 2024)
Although the legal framework regarding Oil and Gas in Indonesia has been regulated through Law Number 22 of 2001 concerning Oil and Natural Gas, in practice, there are still frequent occurrences of misuse in the transportation and distribution of subsidized fuel oil, particularly kerosene and Liquefied Petroleum Gas (LPG). This study aims to examine the investigation process of subsidized fuel and LPG misuse cases within the jurisdiction of the Bali Regional Police (Polda Bali), as well as to analyze the legal measures undertaken by the Bali Regional Police to combat such criminal acts, with reference to the District Court Decision Number 958/Pid.Sus/Lh/2021/PN Dps. This research adopts an empirical legal research method with a descriptive approach, utilizing both primary and secondary data collected through interviews and documentation techniques. The theoretical framework applied includes the theory of the rule of law, the theory of law enforcement, the theory of legal certainty, and the theory of crime prevention. The research findings indicate that law enforcement against the hoarding and misuse of subsidized fuel within the Bali Police jurisdiction has not been effective, as evidenced by an increasing trend of violations over the past three years. The police's efforts to address these offenses involve pre-emptive, preventive, and repressive measures. In conclusion, despite the existence of legal regulations, the effectiveness of enforcement remains suboptimal, necessitating stronger implementation and inter-institutional coordination to reduce the misuse of subsidized fuel and LPG in Bali.